Rational Learners and Moral Rules. (November 2016) - Nichols, Shaun; Kumar, Shikhar; Lopez, Theresa; Ayars, Alisabeth; Chan, Hoi‐Yee
Abstract: People draw subtle distinctions in the normative domain. But it remains unclear exactly what gives rise to such distinctions. On one prominent approach, emotion systems trigger non‐utilitarian judgments. The main alternative, inspired by Chomskyan linguistics, suggests that moral distinctions derive from an innate moral grammar. In this article, we draw on Bayesian learning theory to develop a rational learning account. We argue that the 'size principle', which is implicated in word learning, can also explain how children would use scant and equivocal evidence to interpret candidate rules as applying more narrowly than utilitarian rules.